Formulasi dan uji aktivitas antioksidan sediaan hand body cream ekstrak kulit pisang emas menggunakan metode FRAP - Ayuningsih, Qurotha; Septiarini, Anita Dwi; Veranita, Weri (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2023)
ABSTRACT Antioxidants are chemical compounds that, in certain amounts, can reduce or slow down damage caused by free radical oxidation processes. The content of compounds that have the potential as antioxidants is golden banana skin (Musa acuminata). This study aims to find out whether golden banana peel extract can be formulated into hand and body cream, whether the hand and body cream formulation of golden banana peel extract meets the requirements for good preparation evaluation, and whether the formulation of hand and body cream preparation with golden banana peel extract has antioxidant activity by the FRAP method. This research is a laboratory experimental research conducted by collecting and identifying plant materials and simplicia characteristics, making extracts, testing the correct antioxidant levels in the dosage formulations, and conducting antioxidant activity tests for hand and body cream preparations of golden banana peel extract using the FRAP method. The test results of the golden banana peel (Musa acuminata) can be formulated into hand and body cream preparations, with the best results in formulation 5, which consists of 3% extract with an average antioxidant activity value of 86.118 mgAAE/gram, which indicates the formulation of hand and body cream extract preparations. Mas banana peel has antioxidant activity with the FRAP method. The formulation of hand and body cream preparations with golden banana peel extract can meet the evaluation requirements for good hand and body cream preparations.   Keywords: Antioxidants, Golden Banana Peel, Hand and Body Cream   ABSTRAK Antioksidan adalah senyawa kimia yang dalam jumlah tertentu dapat mengurangi/ memperlambat kerusakan akibat proses oksidasi radikal bebas. Kandungan senyawa yang berpotensi sebagai antioksidan yaitu kulit pisang emas (Musa acuminata). Penelitian ini bertujuan untuk mengetahui apakah kulit pisang emas dapat diformulasikan menjadi hand and body cream, untuk mengetahui apakah formulasi sediaan hand and body cream ekstrak kulit pisang emas memenuhi syarat evaluasi sediaan yang baik serta mengetahui apakah formulasi sediaan hand and body cream ekstrak kulit pisang emas memiliki aktivitas antioksidan dengan metode FRAP. Penelitian ini merupakan penelitian eksperimen laboratorium dengan melakukan pengumpulan serta identifikasi bahan tumbuhan, karakteristik simplisia, pembuatan ekstrak, pengujian kadar antioksidan yang tepat dalam formulasi sediaan serta melakukan uji aktivitas antioksidan sediaan hand and body cream ekstrak kulit pisang emas menggunakan metode FRAP. Hasil pengujian kulit pisang emas (Musa acuminata) dapat diformulasikan menjadi sediaan hand and body cream dengan hasil terbaik pada formulasi 5 yang terdiri dari 3% ekstrak dengan nilai rata-rata aktivitas antioksidan sebesar 86,118 mgAAE/gram yang menandakan Formulasi sediaan hand and body cream ekstrak kulit pisang mas memiliki aktivitas antioksidan dengan metode FRAP. Formulasi sediaan hand and body cream ekstrak kulit pisang emas dapat memenuhi syarat evaluasi sediaan hand and body cream yang baik.   Kata kunci: Antioksidan, Kulit Pisang Emas, Hand and Body Cream